Notodonta dedmazai sp. nov., a new notodontid moth from Bhutan - Schintlmeister, Alexander (Zootaxa, 2013)
Recently, a small series of an unidentified notodontid moth from Bhutan was presented to me by Pavel Morozov (Moscow). The moth is described below, and represents a hitherto unknown species of the holarctic genus Notodonta Ochsenheimer, 1810 and the first record for the genus in the Himalayas.